Lactulose vs Lactuloseand inulin in treatment of pediatric constipation - Sabah Berdawd, Salar; Loqa Hanna, Sasan; Kakameen Hamad , Yasir (Diyala Journal of Medicine, 2023)
Background: Assess the efficacy of combining fiber and lactulose in the treatment of constipation in the pediatric age group. Objective: To assess the efficacy of combining fiber and lactulose in the treatment of constipation in the pediatric age group. Patients and Methods: One hundred forty-six patients with fuctionalconstipation were chosen in a non-randomized superiority trial manner as they were convenient to enroll due to their presentation to the outpatient clinic during the period from August 2019 to February 2022.Patient received either a solution of lactulose 3.3g/5ml in group A or a solution of 4.005g Inulin fiber and 4.005g lactulose per 20ml in group B. Results: Total of 146 children were included; all, 146 patients completed the study. In the lactulose group, 19 patients were on therapy for less than 6 months, and 48 were on therapy for more than 6 months. In the lactulose + fiber group, 59 patients were on therapy for less than 6 months, and 20 were on therapy for more than 6 months. No serious adverse effects were registered but 18 (27%) of children in the lactulose group encountered side effects, while 11 (14%) of children in the lactulose + fiber group encountered side effects. Conclusion: A solution of Lactulose + fiber is superior to a solution of Lactulose alone in terms of efficacy for the treatment of constipation in the pediatric age group. It also has a lower side effects profile.